Biofilms in plant-based fermented foods: Formation mechanisms, benefits and drawbacks on quality and safety, and functionalization strategies. (October 2021) - Gong, Chuanjie; He, Yunxiang; Tang, Yao; Hu, Rong; Lv, Yuanping; Zhang, Qisheng; Tardy, Blaise L.; Richardson, Joseph J.; He, Qiang; Guo, Junling; Chi, Yuanlong
Abstract: Background: In order to balance human health and environmental sustainability, plant-based diets have been attracting increasing attention. Plant-based fermented foods are produced using vegetables or fruits as the main raw materials. Thereafter, microorganisms and their metabolites convert these into the final products, which are often covered by biofilms during production and storage. The biofilms are composed of various microbial flora and extracellular metabolites produced during fermentation, which is generally considered as a shortcoming of fermentation. However, growing evidence suggests that these complex microbial ecosystems are sources of both probiotic substances and antimicrobial compounds, which can benefit health and improve food processing. Scope and approach: Advanced studies have established relationships between the representative film-forming microorganisms in biofilms and the quality and safety of fermented foods. Inhibition and elimination strategies have also been proposed by targeting biofilm control methods from the food and medical industries towards the formation mechanisms and compositional characteristics of the biofilms. Key findings and conclusions: Based on the data generated from previous control measures, this review introduces the key elements pertaining to biofilm formation as function of substrate and metabolic conditioning and summarizes the potential benefits of biofilms, especially in plant-based fermented foods. Further, this review highlights strategies surrounding the utilization and modulation of biofilms in plant-based fermented foods. The re-design and functionalization of biofilms are therefore discussed for a wide range of applications. Highlights: Benefits and drawbacks of biofilms for plant-based fermented foods. Trends in biofilms controlled via physical and biological methods. Biofilms as starters to trigger the fermentation of plant-based foods. Functional biofilms as probiotic substances and antimicrobial materials. Outlooks on bioengineering the metabolic plasticity of biofilms.